Optimization of Cellulase and Xylanase Productions by Streptomyces thermocoprophilus TC13W Using Low Cost Pretreated Oil Palm Empty Fruit Bunch - Santat Sinjaroonsak (2020)
© 2019, Springer Nature B.V. Abstract: The cellulase and xylanase productions from the pretreated empty fruit bunch as the low-cost substrate in a submerged fermentation were investigated. The objectives of this study were selected the local strain that produced high cellulase and xylanase and enhanced the enzymes production by the selected strain. Ten Streptomyces strains were cultivated in the complex medium [(g/l); CaCl2·2H2O 0.1, MgSO4·7H2O 0.1, KH2PO4 0.5, K2HPO4 1.0, NaCl 0.2, NH4NO3 1.0, yeast extract 5.0 and Tween 80 0.5 with alkaline peroxide pretreated empty fruit bunch (APEFB) 20 in distilled water, pH 7.0] in an incubator shaker at 150 rpm and 45 °C for 120 h. The strain TC13W gave the highest cellulase and xylanase activities (280 and 878 U/g APEFB, respectively). This strain was identified by 16S rDNA method as Streptomyces thermocoprophilus (96% similarity). Cellulase and xylanase productions by S. thermocoprophilus TC13W in the optimized medium with 1% (w/v) APEFB and 0.5% (w/v) yeast extract, pH 6.5 at 150 rpm and 40 °C for 120 h gave the maximum cellulase and xylanase activities of 925 and 1796 U/g APEFB, respectively. The increasing of cellulase and xylanase activities in the optimized medium was 3.30 and 2.04 folds, respectively in comparison to the original medium. These in-house enzymes could be used as the promising candidate enzyme for produce various value-added products via an enzymatic hydrolysis of the lignocellulosic waste. Graphic Abstract: [Figure not available: see fulltext.].